Bi‐allelic pathogenic variants in NDUFC2 cause early‐onset Leigh syndrome and stalled biogenesis of complex I - Ahmad Alahmad; Alessia Nasca; Juliana Heidler; Kyle Thompson; Monika Oláhová; Andrea Legati; Eleonora Lamantea; Jana Meisterknecht; Manuela Spagnolo; Langping He; Seham Alameer; Fahad Hakami; et al. (EMBO Molecular Medicine)
Abstract Leigh syndrome is a progressive neurodegenerative disorder, most commonly observed in paediatric mitochondrial disease, and is often associated with pathogenic variants in complex I structural subunits or assembly factors resulting in isolated respiratory chain complex I deficiency. Clinical heterogeneity has been reported, but key diagnostic findings are developmental regression, elevated lactate and characteristic neuroimaging abnormalities. Here, we describe three affected children from two unrelated families who presented with Leigh syndrome due to homozygous variants (c.346_*7del and c.173A>T p.His58Leu) in NDUFC2, encoding a complex I subunit. Biochemical and functional investigation of subjects’ fibroblasts confirmed a severe defect in complex I activity, subunit expression and assembly. Lentiviral transduction of subjects’ fibroblasts with wild‐type NDUFC2 cDNA increased complex I assembly supporting the association of the identified NDUFC2 variants with mitochondrial pathology. Complexome profiling confirmed a loss of NDUFC2 and defective complex I assembly, revealing aberrant assembly intermediates suggestive of stalled biogenesis of the complex I holoenzyme and indicating a crucial role for NDUFC2 in the assembly of the membrane arm of complex I, particularly the ND2 module.